PENGARUH INSENTIF FINANSIAL DAN LINGKUNGAN KERJA FISIK TERHADAP SEMANGAT KERJA KARYAWAN PT BAJA DIVA MANUFAKTUR PEKANBARU - Angga Kurniawan Putra; Dewita Suryati Ningsih; Arwinence Pramadewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
purpose of this study was to determine the effect of financial incentives, and physical work environment on employee morale PT Baja Diva Manufacturing Pekanbaru. Total population in this study were all employees of PT Baja DivaManufacturing Pekanbaru, consisting of 42 employees and a sample is drawn from the entire population consisting of employees of PT Baja Diva Manufacturing Pekanbaru totaling 42 people. Results of the study simultaneously there are significant financial incentives, physical work environment, on morale. The magnitude of the coefficient of determination (Adjusted R Square) = 0263 which means that the contribution of financial incentives, physical work environment on morale was 26.3%. Advice can be given that the employees inorder to continue to develop the ability continuously to carry out the task, to the leadership of the PT Baja Diva Manufacturing Pekanbaru to always strive to provide and increase the number of financial incentives to employees so that employees are satisfied with the incentive money received and feel better eager to work with the incentives and always improve the physical working environment such as the completeness of infrastructure and facilities in the works so that the number of existing employees seesuai the number of equipment and facilities available.Keywords: Financial Incentives, Physical Work environment and Morale.